Escherichia coli Contamination of Water for Human Consumption and Its Associated Factors in Peru: A Cross-Sectional Study - Hernández-Vásquez, Akram (2023)
The objective of the study was to determine the factors associated with the presence of Escherichia coli contamination in water supplies for human consumption in Peru. A secondary analysis of the Food and Nutrition Surveillance by Life Stages survey (VIANEV) of 2017-2018 was performed. The presence of E. coli contamination in the water samples for human consumption of the households evaluated was defined as a dependent variable. A supply was considered contaminated when there was at least 1 colony-forming unit of E. coli in 100 mL of water for human consumption. Data from 886 participants were analyzed. It was found that 25.2% of household water supply sources for human consumption had E. coli at the time of sampling. Water reservoirs such as buckets or other containers (adjusted prevalence ratio [aPR]: 1.15; 95% confidence interval [CI]: 1.18-1.93), households belonging to a poor wealth quintile (aPR: 1.82; 95% CI: 1.01-3.25), residing in a rural area (aPR: 1.36; 95% CI: 1.01-1.83), and having a low human development index (aPR: 2.12; 95% CI: 1.15-3.91) were more likely to contain E. coli in water supplies for human consumption. However, households with chlorine concentrations of 0.5 mg/L or more in water (aPR: 0.20; 95% CI: 0.11-0.33) and with household members with a higher education (aPR: 0.67; 95% CI: 0.45-0.99) were less likely to contain E. coli in drinking-water supplies. From 2017 to 2018, one in four Peruvians had contamination by E. coli in the water supply to their homes, which was associated with sociodemographic factors, management, and water treatment.